Does living Christianity support personhood theism?. Issue 5 (20th October 2022) - Hewitt, Simon
ABSTRACT: Personhood theism is the view that God exists and is a person. It is often claimed that, whatever conclusions might be reached abstractly by philosophers and theologians, Christianity as lived out practically embodies belief in personhood theism. In this article, I critically examine this claim and argue that Christian prayer and liturgical practice does not in fact embody this belief and that the claim that it does begs the questions against the non-personhood theist.